Squamous cell carcinoma of lower lip in very young brothers of xeroderma pigmentosa - A Hemant Saraiya; Mukul Trivedi; Jayesh Patel; J T Jhala (Indian Journal of Plastic Surgery)
a nine-year-old xeroderma pigmentosa (xp) child presented with a non-healing ulcer on the right side of the lower lip. on histological examination the lesion proved to be squamous cell carcinoma. wide excision was done. the excision included lip, buccal mucosa with mucocutaneous junction and only the upper portion of the orbicularis oris muscle. the lip was reconstructed with superiorly based nasolabial flap. recently, his younger brother, who is also suffering from xp developed squamous cell carcinoma of lower lip, and presented to us. wide excision of the lesion was done. the defect was closed primarily. the patient and his brother both have been advised to protect themselves from uv radiation. both are being kept under intense surveillance. ten months of follow-up of the elder brother showed satisfactory, good-looking lip with no sign of recurrence at the local site or at the neck.